Konsep dan Metode Penyelesaian Hitungan Bagian Warisan Dalam Kasus Waris Islam; Analisis dan Aplikatif - Sumper Mulia Harahap; Raja Ritonga (Al-Mizan (e-Journal), 2022)
Completion of the calculation of the inheritance share often triggers internal family conflicts. The calculation of inheritance in fiqh mawaris is assumed to be very complicated and convoluted. As a result, many settlements of inheritance cases in the family have resulted in disputes and disputes. This study aims to explain the method of settlement of Islamic inheritance cases. The qualitative method was chosen in this study with the type of library research. The data used is the result of a search from books, and other scientific works that have relevance to the research theme. The results of the study explain that the settlement of Islamic inheritance cases must go through several stages; identification of heirs, determination of shares, ta'shil (finding the origin of the problem), tashhih (finding the divisor of numbers that cannot be divided even), ascertaining the total amount of inheritance and then dividing the total number of assets by the number of origins of the problem. Then, the results of the study also describe that the settlement of Islamic inheritance cases is categorized into four criteria; the at-tamatsul case, the at-tadakhul case, the at-tawafuq case, and the at-tabayun case.